NAVIGATING THE DEVELOPING LEXICOLOGICAL LANDSCAPE: A SYSTEMATIC LITERATURE REVIEW - Hamuddin, Budianto; Yuliandri, Windi (ELite Journal : International Journal of Education, Language and Literature, 2025)
It is hoped that the basis of linguistics is related to the use of the systematic literature review or SLR research method. This SLR method can dig deeper and be more precise so that it can observe, study, assess and interpret existing research and of course it will be interesting to discuss, especially the discussion here is about the basics of linguistics, And the discussion of lexicology is very dynamic because changes occur in society from time to time and social phenomena always continue to change in society, in this SLR method it is very good to be applied in research, it is related to the science of lexicology, in this SLR method reviews can be carried out or reviewing a journal, article, book, or other type of document in a coherent manner and each step follows the procedures or rules that have been determined. So that the final results of the research can show accurate results without engineering and are more compatible.